Investigating the Dimensions of Inter-Sectoral Cooperation in Preventing Traffic Accidents in Iran: A Qualitative Study - Habib Rezaei; Soad Mahfoozpour; Somayeh Hesam; Eiravan Masoodi Asl (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: Traffic accidents are a principal challenge in the injury and death of people in Iran and many other countries, which has made the formulation of necessary strategies and planning for inter-sectoral cooperation to prevent and reduce traffic accidents undeniable. Therefore, this research was conducted to investigate the dimensions of inter-sectoral collaboration in preventing traffic accidents in Iran. Methods: This research is a qualitative study that was conducted in 2023. In this study, sampling was done in a targeted manner, and 15 people from the statistical population were interviewed. The statistical population of the research at this stage included executive managers, traffic police, field activists, and public institutions active in the field of traffic accidents in Central Province and Tehran, who, due to the relevance of their job field, were informed or participated in intersectoral cooperation in line with the management of accidents and traffic accidents were included in the study. Data were collected and analyzed through structured interviews, and their coding was done with the help of MAXQDA 11 software. Results: The study identified and extracted eight main dimensions of intersectoral cooperation in preventing traffic accidents. These dimensions include laws and law enforcement, research and development, information and data management, internal and external coordination, crisis management, education and awareness, roads, and vehicles. Conclusions: Providing platforms for promoting the development and expansion of inter-sectoral cooperation in accident prevention and traffic accidents can have various benefits, including long-term social, political, economic and, well-being. Therefore, based on the findings of the research, it is suggested to design an intersectoral cooperation model for the prevention of accidents and traffic accidents so that traffic accidents can be reduced to the minimum possible with proper planning and design so that we can witness the highest level of effectiveness and efficiency in this area.